A Multifaceted Strategy to Enhance Glaucoma Knowledge and Reduce Anxiety in the Uyghur Population of Rural China - Jieying Guan; Yingting Zhu; Wenmin Huang; Heping Wu; Rongxin Chen; Yuncheng Ma; Lingling Xie; Junting Kuang; Zixuan Li; Aizezi Wumaier; Yehong Zhuo (Journal of Ophthalmology)
Purpose. The aim of the study is to assess the impact of a multifaceted education strategy for Uyghur patients with glaucoma on their anxiety, satisfaction, and comprehension of disease information in rural China. Methods. This study recruited 100 patients who were randomized into two groups: the control group that received a conventional consultation and the intervention group that received a multifaceted education approach. Information comprehension was evaluated using a 15-item questionnaire. A 6-item State-Trait Anxiety Inventory (STAI-6) score was used to assess patient anxiety levels. Satisfaction was evaluated on the day of discharge. Results. After education, patients in the intervention group scored significantly higher than those in the control group on their knowledge of glaucoma (p≤0.001). Education level, family history of glaucoma, and number of glaucoma clinic visits were independently associated with baseline scores (p = 0.038, 0.002, and 0.017, respectively). The age was negatively correlated with scores (p≤0.001) after education. The STAI-6 score of the intervention group was 28.50 ± 5.13, which was significantly lower than that of the control group (32.50 ± 6.47, p = 0.001). Income levels were negatively correlated and the duration of glaucoma was positively correlated with STAI-6 scores (p≤0.001 and p=0.003, respectively). Overall satisfaction was significantly higher in the intervention group (p≤0.001). The knowledge score was positively correlated with overall satisfaction and follow-up probability (both p≤0.001). The STAI-6 score was negatively correlated with overall satisfaction and follow-up probability (p=0.017 and 0.006, respectively). Conclusions. This new multifaceted educational strategy can enhance patients’ knowledge of glaucoma, reduce their anxiety, and improve their satisfaction. ClinicalTrials.gov (No. 2100050926)